2016
DOI: 10.2118/173801-pa
|View full text |Cite
|
Sign up to set email alerts
|

Low-Salinity Surfactant Flooding—A Multimechanistic Enhanced-Oil-Recovery Method

Abstract: Summary We have applied UTCHEM-IPhreeqc to investigate low-salinity (LS) waterflooding and LS surfactant (LSS) flooding. Numerical-simulation results were compared with laboratory experiments reported by Alagic and Skauge (2010). UTCHEM-IPhreeqc combines the UTCHEM numerical chemical-flooding simulator with IPhreeqc, the United States Geological Survey geochemical model. The IPhreeqc model was coupled to UTCHEM to model LS waterflooding as a function of geochemical reactions. The surfactant core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Generally, surfactants are categorized into four main groups: anionic, cationic, zwitterionic, and nonionic based on their charge of the hydrophilic group. Although a large amount of work has been carried out, , there is a lack of data for low salinity floods, which are a relatively new development. , …”
Section: Introductionmentioning
confidence: 99%
“…Generally, surfactants are categorized into four main groups: anionic, cationic, zwitterionic, and nonionic based on their charge of the hydrophilic group. Although a large amount of work has been carried out, , there is a lack of data for low salinity floods, which are a relatively new development. , …”
Section: Introductionmentioning
confidence: 99%
“…The stability of the displacement front in the LSW/LSS process is a critical issue to achieve a successful recovery. Tavassoli et al [50] showed that unstable fronts of surfactant floods due to the high velocity result in slow oil recovery. This problem can be solved through the combination of LSW with surfactant/polymer (SP).…”
Section: Lsw/surfactant Hybrid Eor Techniquementioning
confidence: 99%
“…The lack of modeling and optimization of the process through simulation studies is obvious in this field. In [50], Tavassoli et al applied UTCHEM-IPhreeqc to model LSW as a function of geochemical reactions and surfactant flooding. Their simulations were in good agreement with experiments carried out by [27].…”
Section: Lsw/surfactant Hybrid Eor Techniquementioning
confidence: 99%
“…The loss of surfactant from the driving fluid during the flooding operation decreases the availability of surfactant for interactions with the oil phase, which hampers the reduction of the interfacial tension between the oil/water system and consequently the detachment and mobilization of residual oil. [1][2][3][6][7][8][9][10]12,14,19,20,23 In reality, it is impossible to fully inhibit surfactant losses onto reservoir rock during flooding operations; nevertheless, surfactant losses must be controlled to some extent because surfactants are expensive 21,24−27 and "the successful implementation of surfactant flooding EOR process depends mainly on the cost of surfactants" (Belhaj et al (2020) 1 ).…”
Section: Introductionmentioning
confidence: 99%